SIFAT FISIK DAN MEKANIK PAPAN SEMEN PARTIKEL DARI LIMBAH FINIR BERDASARKAN KOMPOSISI BAHAN DAN UKURAN PARTIKEL - Saraswaty, Dhian; Dirhamsyah, M; Indrayani, Yuliati (Universitas Tanjungpura, 2018)
This study aims were to examine the effect of material composition, particle size and the interaction of both factors on the physical and mechanical properties of particle-cement board from veneer waste, and to determineÂ the optimal material composition and particle size of particle-cement board accordance to JIS A 5417:1992. The research were conducted at Wood Workhsop Laboratory, Wood Technology Laboratory, Wood Processing Laboratory of Tanjungpura University and Laboratory of PT. Duta Pertiwi Nusantara Pontianak. The materials used were veneer waste, portland cement-type 1 (Holcim), 70% of tap water from weight of cementÂ and 5% of MgCl2 from weight of cement. The data were analyzed using a factorial experiment in random design complete (RDC) which consists of two factors. Factor A was material composition (cement:particle) consists of 75:25, 80:20, 85:15. Factor B was particle size consist of 20 mesh and 40 mesh. The board were made with size of 30 cm x 30 cm x 1 cm and with target density of 1 gr/cm3. The pressing was done by manual cold press for 10 minutes, followed by clamping the board for 24 hours with iron clamp. The result showed that the material composition and the interaction of both factors had significant effects on density, moisture content, thickness swelling, MOE and MOR. The particle size factor had Â significant effects on density, moisture content, thickness swelling, water arbsoption, MOE and MOR. The board produced which fullfil the JIS A 5417:1992 was made with the treatment with composition cement:particle (85:15) and particle size is 40 mesh.Keyword: material composition, particle size, particle-cement board, physical and mechanical properties, veneer waste.